STRATEGI PENCEGAHAN DAN INTERVENSI CYBERBULLYING UNTUK MENINGKATKAN KESEHATAN MENTAL MAHASISWA - Siti Aisah Azzahra; Edy Soesanto; Zahra Dwiana Febrianti (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Cyberbullying is a detrimental act carried out by a person or certain group in various ways, such as sending rude text messages, degrading photos, sensitive meme images, sensitive videos, and spreading personal information about someone through digital media such as someone's social media. the aim is to harass, insult, insinuate, or lower the self-esteem of other people. The aim of this research is to analyze the impact of cyberbullying on students' mental health, discuss prevention strategies that can be applied in educational environments, review the effectiveness of cyberbullying interventions in helping students who are victims, and identify changes in students' mental health after efforts to implement prevention and intervention strategies. The research method used is a literature review, which combines previous research from relevant literature sources on the theme of cyberbullying. The database was chosen with the consideration that 15 journals and articles were relevant to the 2016-2023 period, using a combination of keywords: cyberbullying, mental health, and students. The results showed that cyberbullying had a significant negative impact on college students' mental health, including depression, anxiety, and low self-esteem. Factors that exacerbate cyberbullying include individual factors, groups, mentors, schools, and internet use. Acknowledging these factors can help develop more effective prevention strategies. Conclusion: According to the research mentioned, cyberbullying has a significant negative impact on the mental health of high school students, including depression, anxiety, and low self-esteem. This emphasizes how important it is to understand and solve this problem. Several strategies can be implemented to prevent cyberbullying and protect the mental health of high school students. Among these are education and training, computer skills, social networking, scanning and screening, one-on-one instruction, counseling, legal advice, positive reinforcement, and further research. Further studies and continued efforts to prevent and overcome cyberbullying need to be carried out to create a safe and healthy environment for students.